The Analysis of Waqf Reporting Practices and Waqf Information Disclosure: A Study at Perbadanan Wakaf Selangor, Malaysia - Hisham, Mohd Firdaus Badrul; Muwazir, Mohd Rizal (Humanities and Social Sciences Letters, 2022)
Disclosure of information related to waqf in the annual financial report is crucial to increase the level of confidence amongst Muslim communities and stakeholders in waqf institution. Due to the non-transparency and lack of disclosure by waqf institutions, it is difficult to ascertain whether the donated waqf assets can be utilized properly or otherwise. The objective of this study was to identify the practice of waqf information disclosure at Perbadanan Wakaf Selangor (PWS) from 2014 until 2019. This study is quantitative in nature by applying the content analysis method which focuses on counting and measuring themes in annual reports. This study found that PWS has successfully disclosed a good, transparent and quality waqf financial reporting as it obtained 86% in the waqf reporting disclosure index each year. The study’s findings concluded that PWS followed the standards and reporting format set by the accounting body and successfully disclosed full information to stakeholders and the Muslim community in Malaysia.